Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/ajhb.21027
|View full text |Cite
|
Sign up to set email alerts
|

The effect on energy expenditure of walking on gradients or carrying burdens

Abstract: The effectiveness of people walking while carrying burdens and/or on gradients has been of interest to anthropologists for some time. No empirical equation exists, however, to assess the energetic expenditure of individuals traveling downhill with burdens and whether or not all people increase their energetic expenditure over unburdened level travel when carrying relatively light burdens (<20% of body mass) remains unclear. To begin to rectify this lacunae, gait parameters, physiological variables, and the ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 88 publications
1
28
0
2
Order By: Relevance
“…Different approaches have been taken to investigate the load transport economy. The absolute amount of oxygen consumed (Chung, Lee, Lee, & Choi, ); the amount of oxygen consumed relative to body mass (Lloyd & Cooke, ), or to total mass (body mass + carried load) (Balogun et al, ); the energy cost of locomotion (Abe, Yanagawa, & Niihata, ), the energy of walking and carrying burdens (Kramer, ); or the net metabolic power (Bastien, Willems, Schepens, & Heglund, ) have been reported to properly reflect the energetic cost of burden transport. Nonetheless, following Lloyd, Hind, Parr, Davies, and Cooke (), the cost of transporting a load is best represented by factoring out the energy cost of unloaded walking.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been taken to investigate the load transport economy. The absolute amount of oxygen consumed (Chung, Lee, Lee, & Choi, ); the amount of oxygen consumed relative to body mass (Lloyd & Cooke, ), or to total mass (body mass + carried load) (Balogun et al, ); the energy cost of locomotion (Abe, Yanagawa, & Niihata, ), the energy of walking and carrying burdens (Kramer, ); or the net metabolic power (Bastien, Willems, Schepens, & Heglund, ) have been reported to properly reflect the energetic cost of burden transport. Nonetheless, following Lloyd, Hind, Parr, Davies, and Cooke (), the cost of transporting a load is best represented by factoring out the energy cost of unloaded walking.…”
Section: Introductionmentioning
confidence: 99%
“…Because previous work [65] indicated that considerable between individual variability exists in walking and that at least some of this variability is due to physiological factors for which we are not currently able to control, we wanted to distinguish variability that exists within an individual from that which exists between individuals. This is important because it provides information regarding the degree to which the method accounts for these two sources of variation (within and between individuals).…”
Section: Methodsmentioning
confidence: 99%
“…(1), a best-fit theoretical equation for gradient walking is used to calculate energy expenditure. It could explain 87% of the variation in energetic expenditure [11]. …”
Section: F Digitization Of Mountain Trail and Calculation Of Energy mentioning
confidence: 99%